2017
DOI: 10.1080/00028487.2017.1313778
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Ecology, Spawning Behavior, and Juvenile Distribution of Mountain Whitefish in the Madison River, Montana

Abstract: Mountain Whitefish Prosopium williamsoni were historically common throughout much of the U.S. Intermountain West. However, within the last decade Mountain Whitefish have exhibited population‐level declines in some rivers. In the Madison River, Montana, anecdotal evidence indicates Mountain Whitefish abundance has declined and the population is skewed toward larger individuals, which is typically symptomatic of recruitment problems. Describing reproductive development, spawning behavior, and juvenile distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 49 publications
0
22
1
Order By: Relevance
“…A separate experiment described in the original 2007 report (Schisler 2010) suggests that Mountain Whitefish are highly, if not completely, resistant to infection by M. cerebralis at 5 months (15,000 degree‐days), even when exposed to 10,000 actinospores per fish (Schisler 2010). In the Blackfoot and Madison rivers in Montana, Mountain Whitefish fry spawn in the fall (October and November) and hatch in the spring (February through April) (Pierce et al 2012; Boyer et al 2017). In these rivers, peak actinospore production occurs between May and July (Downing et al 2002; Pierce et al 2009) when Whitefish are 1–5 months posthatch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate experiment described in the original 2007 report (Schisler 2010) suggests that Mountain Whitefish are highly, if not completely, resistant to infection by M. cerebralis at 5 months (15,000 degree‐days), even when exposed to 10,000 actinospores per fish (Schisler 2010). In the Blackfoot and Madison rivers in Montana, Mountain Whitefish fry spawn in the fall (October and November) and hatch in the spring (February through April) (Pierce et al 2012; Boyer et al 2017). In these rivers, peak actinospore production occurs between May and July (Downing et al 2002; Pierce et al 2009) when Whitefish are 1–5 months posthatch.…”
Section: Discussionmentioning
confidence: 99%
“…They are an ecologically important forage fish for upper trophic predators, including the threatened endemic Bull Trout Salvelinus confluentus , and are a common target for anglers (Pierce et al 2012). Declines in Mountain Whitefish populations have been observed across many river systems since the 1990s, including in the Blackfoot and Madison rivers in Montana (Pierce et al 2012; Boyer et al 2017), the Big Lost and Kootenai rivers in Idaho (Elie 1997), and the main stem and tributaries of the Yampa River (Schisler 2010). The causes of these declines are not known but may relate to rising stream temperatures (Brinkman et al 2013), toxicity from mining and agricultural runoffs (Brinkman and Viera 2008; Quinn et al 2010), and stream modification (Kennedy 2009).…”
mentioning
confidence: 99%
“…Montana system, Boyer et al (2017) found no evidence that MW select for specific depths, water velocity or substrate composition at spawning sites. This was evident in the fish in my study which showed increased depth residency in winter and spring, but no depth bin preference.…”
Section: Reach and Depth Residencymentioning
confidence: 82%
“…Pierce et al (2012) noted a that over 30% of the adult MW showed no migratory spawning movements during the spawning season. Boyer et al (2017) also noted that a proportion of adult MW remained in close proximity to spawning grounds throughout the spawning period. As I did not directly monitor specimens to confirm spawning activity, it is also possible that MW selected these locations for foraging or overwintering purposes (Northcote 1997).…”
Section: Reach and Depth Residencymentioning
confidence: 86%
See 1 more Smart Citation